Identification and characteristics of MYB4 transcription factor related to regulation of abiotic stress tolerance in peanut - Kha, Hoang; Nguyen, Quang Duc Tien (Hue University Journal of Science: Natural Science, 2024)
Peanut (Arachis hypogaea L.), an economically valuable crop, provides protein and oil for human and animal consumption. The transcription factor MYB4 has been identified as a potential drought tolerance gene in peanut. This study aimed to isolate and characterize the MYB4 gene in the L14 peanut cultivar. The isolated AhL14_MYB4 gene was found to be 1.1 kb long, with a 663 bp coding sequence containing 3 exons and 2 introns. In silico analysis showed that AhL14_MYB4 possesses a nuclear localization signal and two DNA-binding domains characteristic of transcription factors. The findings revealed key molecular features of AhL14_MYB4 and provided insights into improving drought resistance in peanut varieties. Further research on AhL14_MYB4 may aid efforts to enhance drought tolerance in local peanut cultivars through molecular breeding or genetic engineering. Overall, this finding about preliminary characterization of the peanut MYB4 gene lays the groundwork for potential genetic improvements to this economically important crop.